Justice Scalia and the Religion Clauses: A Comment on Professor Epps - Eric R. Claeys (Washington University Journal of Law & Policy, 2006)
In this Comment, I hope to identify the areas in which Professor Epps makes novel and important insights, and the areas in which originalists and religionists will disagree with how he evaluates those insights.
Keywords: Free exercise clause (Constitutional law); Establishment clause (Constitutional law); Originalism (Constitutional interpretation); Antonin Scalia; 1936-; Church and state; Freedom of religion; United States Constitution; United States; Garrett Epps